Technical visit to Faculty of Engineering, USM and Boustead Penang Shipyard (Pulau Jerejak) Malaysia - Muhammad Hilmi, Raja A. Aziz (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org